Influences of Constitutive Models and Strain Path on Predicted Forming Limit Curves for AA5182-0 Alloy - Basti, Ali; Sojodi, Soheila; Falahatgar, Seyed Reza; Mirfalah Nasiri, Seyedeh Maryam (Mechanical Technology and Engineering Insights, 2025)
The onset of necking in a metal forming process is usually predicted by the Forming Limit Curve (FLC). Different hardening laws and yield criteria are employed to describe the plastic behavior of the AA5182-0 aluminum sheet, and their constant parameters are determined. Results indicated that the calculated FLC based on the modified Kim-Tuan and Yld2000-2d yield function can predict the experimental data better than other models. Because of the complexity of the metal forming process, the loading path is rarely linear, therefore, forming limits should be computed in nonlinear strain path conditions. Theoretical FLCs show that the strain path has a notable influence on the limit strains, and the path dependency of the Forming Limit Stress Curve (FLSC) is much less than limit curves in strain space. It was found that in multistep loading processes, limit stresses are affected by strain path when the pre-effective strain reaches a critical value, and this value is sensitive to selected constitutive models. Therefore, the material description has a considerable effect on the path dependency of forming limit stresses. Consequently, at the end of this study, effects of hardening models and yield functions on the sensitivity of the FLSC to strain path are examined.